Population Structure and Genetic Diversity of Agave Germplasms in China - Xiaoli Hu; Yubo Li; Shibei Tan; Lisha Chen; Dietram Samson Mkapa; Chen Lin; Qingqing Liu; Gang Jin; Tao Chen; Xu Qin; Kexian Yi; Xing Huang (Agronomy)
Agave hybrid cultivar 11,648 has been planted for sisal fiber production in China since the 1960s. However, little is known about the population structure and genetic diversity of agave germplasms in China. Therefore, we developed a group of core SNP markers to evaluate the population structure and genetic diversity of 125 agave germplasms in China, including 20 cultivars, 14 breeding lines, and 89 transplanted resources from different areas. Cost-effective amplicon sequencing technology was used to identify genetic variants. The results grouped most cultivars and breeding lines together, which indicated that local agave breeding programs aimed to improve fiber and disease-resistance traits. These breeding programs have reduced genetic diversity, even with the gene flows from other Agave species. The neighbor-joining phylogenetic tree revealed the relationships between A. H11648 and its parents. The phylogenetic relationship between A. sisalana and A. amanuensis is doubtful, even if they are considered heterotypic synonyms. The 11 agave germplasms introduced from Mexico suggest the abundant diversity of agave germplasms in Mexico, which is also the source of agave germplasms in China. This study provides a sketch map for agave germplasms in China, which will benefit future studies related to population genetics and breeding works of agave.